An Ayurvedic Approach to Secondary Amenorrhea as a Manifestation of Premature Ovarian Failure (POF) - Narendra Kumar Meena; Lipakshi Agrawal; Diksha Khathuria (International Journal of Ayurveda and Pharma Research, 2025)
Amenorrhea, the absence of menstruation, is categorized into primary (before menarche) and secondary (after menarche) forms, with significant implications for female reproductive health. Secondary amenorrhea in women of reproductive age may be an indication of an undiagnosed, chronic condition and appropriate treatment is dependent upon accurate diagnosis of the underlying aetiology. According to Acharya Sushruta, Secondary amenorrhoea is described as destruction of Artava (Nashtartava) as well as described it as one of the symptoms of Artava-Vaha Stroto Viddha Lakshana, where he describes that mechanical injury to Garbhashaya i.e. uterus may lead to Artavanasha which means secondary amenorrhoea, this results in infertility. Here, we have described a case study of secondary amenorrhoea due to Premature Ovarian Failure. A 40-year-old married woman came to our OPD of Prasuti Tantra & Stri Roga, M.M.M. Govt. Ayurveda College, Udaipur. with the presenting complaints of absence of menses for 1.5 years, inability to conceive for 18 years. After taking patient history, general examination in which blood pressure (158/110mm hg), BMI (28.1kg/m2) were raised, and thorough investigations reveals there is altered echotexture of uterus with small uterine fibroid in USG we considered the POF as a main cause of Nashtartava (secondary amenorrhoea) and treated with Matra Basti with Lashuna taila and oral intake of Panchkola Churna, Punarnava Mandoora, Balsudha combination, Kaishora Guggulu, Dashmoola Kwatha and got surprising result in secondary amenorrhoea due to POF. The findings also emphasize the need for further research to evaluate long-term outcomes and refine management protocols for both primary and secondary amenorrhea, ultimately aiming to improve patient care and fertility prospects.